2016
DOI: 10.1002/cncr.29907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and treatment factors determining long‐term outcomes for adult survivors of childhood low‐grade glioma: A population‐based study

Abstract: BACKGROUND:The determinants of outcomes for adult survivors of pediatric low-grade glioma (PLGG) are largely unknown. METH-ODS: This study collected population-based follow-up information for all PLGG patients diagnosed in Ontario, Canada from 1985 to 2012 (n 5 1202) and determined factors affecting survival. The impact of upfront radiation treatment on overall survival (OS) was determined for a cohort of Ontario patients and an independent reference cohort from the Surveillance, Epidemiology, and End Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 46 publications
8
101
4
Order By: Relevance
“…Our study included a higher proportion of patients with supratentorial LGG, which was similarly reported by other population‐based studies of LGG. A relatively low incidence of spinal cord LGGs has been reported in other studies as well . We found that receiving both chemotherapy and radiation therapy was a risk factor for higher rates of long‐term facial motor and sensory disorder, lower cranial nerve palsies, eye and visual dysfunction, motor weakness, sleep disturbances, and urinary dysfunction.…”
Section: Discussionsupporting
confidence: 69%
“…Our study included a higher proportion of patients with supratentorial LGG, which was similarly reported by other population‐based studies of LGG. A relatively low incidence of spinal cord LGGs has been reported in other studies as well . We found that receiving both chemotherapy and radiation therapy was a risk factor for higher rates of long‐term facial motor and sensory disorder, lower cranial nerve palsies, eye and visual dysfunction, motor weakness, sleep disturbances, and urinary dysfunction.…”
Section: Discussionsupporting
confidence: 69%
“…Grade I gliomas including pilocytic astrocytoma, pleomorphic xanthoastrocytoma, and subependymal giant cell astrocytoma share a relatively benign biology with an indolent clinical course that is distinct from other diffuse infiltrating glioma grades. 23,24 Grade II–IV gliomas are heterogeneous tumors with variable degrees of infiltration, atypia, and mitotic activity. Microvascular proliferation with endothelial hyperplasia and pseudopallisading necrosis are the defining histological hallmarks of grade IV gliomas, frequently referred to as glioblastomas.…”
Section: Conventional Magnetic Resonance Imaging Featuresmentioning
confidence: 99%
“…As a result, alternative therapeutic strategies are currently used as firstline treatment, reserving radiation for tumors that have progressed despite the use of multiple lines of chemotherapy. 7,12 A strategy combining close observation with systemic chemotherapy if necessary has become the standard of care. 13 Tumor progression, threat to vision and hypothalamic-pituitary dysfunction in the case of an optic pathway glioma, tumor location, residual disease, age of the patient, and association with neurofibromatosis type 1 (NF1) can influence the decision about particular chemotherapeutic regimens.…”
Section: Pediatric Low-grade Gliomasmentioning
confidence: 99%
“…However, due to the tendency of these lesions to be large and to typically affect young children, the potential for radiation‐induced brain injury, with the associated serious cognitive, developmental, and endocrine sequelae in the developing brain, is of major importance. As a result, alternative therapeutic strategies are currently used as first‐line treatment, reserving radiation for tumors that have progressed despite the use of multiple lines of chemotherapy . A strategy combining close observation with systemic chemotherapy if necessary has become the standard of care …”
Section: Introductionmentioning
confidence: 99%